2014
DOI: 10.1177/1049909114540033
|View full text |Cite
|
Sign up to set email alerts
|

Wishes of Patients With Terminal Cancer and Influencing Factors Toward the Use of Antibiotics in Taiwan

Abstract: This study indicated the responsibility of medical professionals to convey burdens of using antibiotics to patients and family. Otherwise, by enhancing professional training and performing effective communication with patients, we can reach a more appropriate decision in the use of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…With regard to the use of artificial nutrition or tube feeding, a Chinese adage says that "hunger breeds discontentment," and accordingly some families may be worried that the patient might die of hunger, and then ask that artificial nutrition or tube feeding is continued for these patients. As for the use of antibiotics in terminally ill patients, previous studies conducted in patients with terminal cancer [34][35][36] and noncancer 22,37 reported that the use of antibiotics for infection was not uncommon. There has been some controversy about decision-making and ethical concerns with antibiotic use in terminally ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the use of artificial nutrition or tube feeding, a Chinese adage says that "hunger breeds discontentment," and accordingly some families may be worried that the patient might die of hunger, and then ask that artificial nutrition or tube feeding is continued for these patients. As for the use of antibiotics in terminally ill patients, previous studies conducted in patients with terminal cancer [34][35][36] and noncancer 22,37 reported that the use of antibiotics for infection was not uncommon. There has been some controversy about decision-making and ethical concerns with antibiotic use in terminally ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…34 Another study reported that 45% of patients with cancer would wish to use antibiotics at a late terminal stage and factors associated with the wish to use antibiotics included familiarity with antibiotics, subjective norms, and attitudes toward the burden of antibiotics. 35 The use of antibiotics in terminal patients requires full discussion and shared decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Among 255 American patients who had advanced cancer and had been taking community-based outpatient hospice and palliative care in 2003, a majority of them (79.2%) chose either no antimicrobial therapy (31%) or symptomatic use only (48.2%) [29]. Other studies performed in Taiwan, which has a distinctive culture deeply influenced by Confucianism and Buddhism, have revealed that 45.8% of the patients with terminal cancer expressed their wish to use antimicrobials even in the very terminal stage and 26.4% did not wish to use antimicrobials [7]. The most influential persons were medical professionals [7].…”
Section: Special Considerations For Antimicrobial Stewardship Programmentioning
confidence: 99%
“…Other studies performed in Taiwan, which has a distinctive culture deeply influenced by Confucianism and Buddhism, have revealed that 45.8% of the patients with terminal cancer expressed their wish to use antimicrobials even in the very terminal stage and 26.4% did not wish to use antimicrobials [7]. The most influential persons were medical professionals [7]. A study on 3,840 Korean individuals (1,242 cancer patients, 1,289 family caregivers, and 303 oncologists) showed that a large majority of individuals supported the withdrawal of futile life-sustaining treatment (87.1 – 94.0%) and use of active pain control (89.0 – 98.4%) [30].…”
Section: Special Considerations For Antimicrobial Stewardship Programmentioning
confidence: 99%
See 1 more Smart Citation